The role of microbial signals in plant growth and development: Current status and future prospects - Al-Ani, Laith Khalil Tawfeeq; Franzino, Théophile; Aguilar-Marcelino, Liliana; Haichar, Feth El Zahar; Furtado, Edson Luiz [UNESP]; Raza, Waqas; Jatoi, Ghulam Hussain; Raza, Mubashar (Elsevier, 2020)
The microbial community is surrounded by plants and this leads to an interaction between them. There are two types of microbials that interact with plant: beneficial microbes and pathogenic microbes. There is a relationship between microbes and plants due to the secretion of many chemical signals. Chemical signals affect the growth and the development of plants depending on the type of microbial. The chemical signals of beneficial microbes produce auxins, gibberellins, indole-3-acetic acid, and nitrogen fixation, which enhance plant growth and development, as well as others signals can confer protection to plants by inducing plant defenses. On the other hand, the plant-microbial pathogens can cause a defect in growth and development for plants by chemical signals. The chemical signals of plant-microbial pathogens include three types such as extracellular enzymes, secondary metabolites, and phytohormones. The chemical signals of plant-microbial pathogens affect three parts of the plant: chloroplasts, mitochondria, and peroxisomes. These parts are the main center for facilitating the plant defenses and play a major role in the repression of the ability of plant pathogens to invade the host plant. Indeed, the role of microbial signals, either beneficial or pathogenic, for the plant in enhancing the plant growth and plant defenses has become clear. This discovery has provided alternative to synthetic chemical such as biopesticides, biofertilizers, bioherbicides, and plant activators. Finally, the microbial signals can be utilized to save the ecosystem from the residues of synthetic chemicals to control plant enemies and enhance plant growth.
Keywords: CMV; FusariumChloroplasts; MAMPs; Mitochondria; PAMPs; Pathogen; Peroxisomes; ROS; Trichoderma